Pregnant? Validity of the Pregnancy Checkbox on Death Certificates in 4 States, and Characteristics Associated With Pregnancy Checkbox Errors. Issue 4 (December 2020) - Catalano, A.; Davis, N.L.; Petersen, E.E.; Harrison, C.; Kieltyka, L.; You, M.; Conrey, E.J.; Ewing, A.C.; Callaghan, W.M.; Goodman, D.A.
Abstract : ( Am J Obstet Gynecol . 2020;222:269.e1–269.e8) The maternal mortality rate (MMR) in the United States appears to be increasing, potentially due to the adoption of the US standard certificate of death. This new death certificate was implemented in 2003 and includes a pregnancy checkbox. While the checkbox was added due to underreporting of maternal mortality, it also makes possible the misclassification of maternal deaths. One review found a 15% false-positive rate, or cases without evidence of pregnancy. This study's aim was to assess the validity of the pregnancy checkbox following a quality assurance process among 4 states examining deaths during 2016.